PENGEMBANGAN VIDEO ANIMASI 3D PEMBELAJARAN LALU LINTAS MENGGUNAKAN SOFTWARE BLENDER - Hardianto Hardianto; Firmanto Firmanto; Afdal Anas; Lisa Aditya Dwiwansyah Musa (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2022)
Learning media that combines audio and visual are very well used in learning, for example learning videos. This study aims to determine the results of expert validation and student responses to 3D animation videos of traffic learning using blender software for seventh-grade students of SMPN 8 Palopo. This research is development research with ADDIE model. The instruments used to collect data in this development research are questionnaires and document analysis. Data were analyzed using descriptive statistical analysis, namely quantitative data obtained from questionnaires in the form of scores which will be processed using formulas and categorized based on criteria. Then qualitative descriptive analysis, namely qualitative data obtained from questionnaires in the form of correction suggestions from the validator. The results showed that the traffic learning 3D animation video developed met the valid and practical criteria, which means that the video is suitable for use in the learning process and gets a good response from students.